Merjenje intelektualnega kapitala v podjetjih terciarne logistike - Zelenika, Ratko (Naše gospodarstvo, 2007)
In enterprises, knowledge has become the capital that helps achieve competitive advantage on the market. The field of intellectual capital is very complex, and therefore difficult to measure. The purpose of this paper is to explore the impact of intellectual capital on the success of logictic companies, to present theoretical characteristics of logistic capital in a simple way, and to give important guidelines for logictics.
Keywords: podjetja; storitve; logistika; intelektualni kapital; knowledge; znanje; merjenje